The Night Nurse: A reflection on On Being Sane in Insane Places by D. L. Rosenhan (1973) - Curwyn Mapaling (University of Johannesburg, 2024)
In this poetic reflection, The Night Nurse draws inspiration from D.L. Rosenhan's influential 1973 study to probe the complex relationship between personal identity and the structural confines of higher education (HE). The poem presents a rich tableau that contrasts indigenous knowledge with Western educational paradigms, shedding light on the friction and marginalisation that arise at the intersection of these worldviews. It embodies the struggle for self-definition amidst a backdrop that often favours uniformity and compliance. By examining the similarities between psychiatric labelling and academic evaluations, the narrative challenges the reader to consider the authenticity of understanding and the significance of diverse perspectives in scholarly environments.